The impact of the strategic sale of restructured banks: evidence from Indonesia - Riyanto, Yohanes Eko (2013)
We examine the effect of strategic sale, which is the sale of banks to strategic foreign investors, on bank performance. The Government of Indonesia implemented such a policy as part of a bank restructuring in the aftermath of the 1998 banking crisis. Using difference-in-differences models, we find that strategic sale leads to a 12–15% cost reduction. These results are robust to the use of other estimators such as difference-in-differences matching estimators and stochastic-frontier analysis, to that of other performance measures such as return on assets and net interest margin, and to that of different sample types. These results suggest that strategic sale could play an important role in restructuring troubled banks in developing countries.